Mechanistic investigation on solar light initiated destruction of indicator bacteria - Lale, Ezgi. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2021., 2021)
Due to the increasing shortage of clean drinking water around the world, some point of use disinfection techniques has been improved to obtain purified drinking water from pathogen microorganisms. Water disinfection using natural or artificial sunlight has been widely studied for the inactivation of microorganisms. Pathogens can be destructed with the synergistic effects of the solar light and thermal heat. Recently, application of solar photocatalysis has gained attraction for the effective inactivation of microorganisms. In this study, solar light initiated destruction of bacteria typically Escherichia coli as the model indicator organism and characterization of the released organic matter were evaluated in the presence/absence of photocatalysts, namely TiO2 and its second generation type Fe-doped TiO2. Via destruction of cell membrane, contents of released proteins, carbohydrates and potassium were determined. Solar photolytic/photocatalytic inactivation of E. coli was conducted in the presence/absence of water matrix that provides the ionic characteristics of natural waters and in the presence/absence of humic acid that is a dissolved organic matter analogue in natural waters, hence the degradation of humic acid by solar light initiated processes in the presence of E. coli was also investigated. Characterization of organic matter in respect of E. coli inactivation was evaluated by specified and specific ultraviolet-visible and fluorescence parameters, dissolved organic carbon contents, and excitation emission matrix fluorescence contour plots. E. coli inactivation was followed by bacteria reduction kinetic parameters, and detection of organic (protein and carbohydrate) and inorganic (K⁺ ion leakage) contents under specified conditions in relation with the spectroscopic parameters.
Keywords: Indicators (Biology); Drinking water.